The Flood Politicization and Social Media: Ecological Disaster, Satire, and the Contestation of the 2024 Indonesia Presidential Election on Twitter - Mustabsyirotul Ummah Mustofa; Muhammad Ridlo Aulia; Rahmah Ramadhani; Karmeta Syahwan Nurfadillah (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
As floods are common in Indonesia, social media are full of conversations about this annual disaster. When floods hit Jakarta, Central Java, South Kalimantan and other areas in early 2021, the most-talked issue in the conversations on social media, especially Twitter, was not about how environmental degradation causes the floods but rather about how the heads of the flooded areas are to compete in the upcoming presidential election. Using critical discourse analysis, this study seeks to explore discourses on the flood politicization related to the 2024 presidential election on Twitter. The results show that there are dominant and marginal discourses in the discussion of the flood issue. The dominant discourse is related to the image and ability of the regional heads to overcome the flood which is linked to his capacity as a presidential candidate in the 2024 election. Meanwhile, the marginal discourse is related to policies taken by regional heads in taking preventive actions and post-flood handling. This article shows findings as follows: first, floods as an ecological disaster which causes environmental management are not an important concern of the community as they are regarded as a common issue that happens every year; second, the flood issue was used to criticise the former governor in a satiric way; third, the flood issue was used as a momentum to test the popularity and electability of candidates for the presidential election as a result of the political division after the 2017 Jakarta Election and the 2019 Indonesian Presidential Election. This article argues that the political debate for the 2024 presidential election in Indonesia was more interesting than the awareness of environmental damage.